Redesain Dan Pengembangan Pelabuhan Sei Duku Di Pekanbaru Dengan Pendekatan Struktur Sebagai Elemen Estetika - Deddi Syafrijon; Ratna Amanati; Mira Dharma Susilawaty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Ports is a facilities of transportasion which still plays an important role in the development of various modes of transport. Especially in Indonesia, known as the MaritimeStates, port as part well as a liaison between the gate area economy. Sei Duku Port is the only port that is located right in Pekanbaru’s downtown, Sei Duku Port plays an important role in the development of Pekanbaru and Riau Province. Along with the times Sei Duku port state currently has some shortcoming such as chaotic circulation, irregular parking area, and don’t accomodate the needs of the water transportation into or out ofPekanbaru. So, it needs to redesign and developing the Sei Duku Port. Redesign and development of the Sei Duku Port apply the structure as an aesthetic element by applying theconcept of tectonics architectural. Application of the theme and concept was done by exposure and processing of the structure of the building so as to overcome the problems that occured on the current port. The result and conclusion of the redesign and development of port activities Sei Duku is, a port must have a regular circulation and grouping and able to accomodate the needs of its users.Key word : Port, sei duku port, the structure as an aesthetic element, the concept of tectonics architectural